Giant seaperch iridovirus infection upregulates Bas and Bak expression, leading to apoptotic death of fish cells. Issue 2 (August 2015) - Chen, Xin-Yu; Wen, Chiu-Ming; Hui, Cho-Fat; Chen, Ming-Chyuan; Wu, Jen-Leih; Hsueh, Tsai-Ching; Lei, Wei-Han; Hong, Jiann-Ruey
Abstract: The giant seaperch iridovirus (GSIV) induces host cell apoptosis by a poorly-understood process. In this study, GSIV is shown to upregulate the pro-apoptotic death genes Bax and Bak at the middle replication stage, and factors in the grouper fin cell line (GF-1) are shown to modulate this process. Studying the mechanism of cell death, we found that upregulated, de novo -synthesized Bax and Bak proteins formed heterodimers. This up-regulation process correlated with mitochondrial membrane potential (MMP) loss, increased caspase-3 activity, and increased apoptotic cell death. All effects were diminished by treatment of infected GF-1 cells with the protein synthesis inhibitor cycloheximide. Interestingly, overexpression of the anti-apoptotic gene Bcl-xL also diminished GSIV-induced mitochondria-mediated cell death, increasing host cell viability and decreasing MMP loss at the early replication stage. Our data suggest that GSIV induces GF-1 apoptotic cell death through up-regulation of the pro-apoptotic genes Bax and Bak, which are regulated by Bcl-xL overexpression on mitochondria in GF-1 cells. Graphical abstract: Highlights: Iridovirus (GSIV) induces host cell apoptosis by an ill-understood process. GSIV can upregulate the pro-apoptotic death genes Bax and Bak at the middle replication stage. Pro-apoptotic gene Bax and Bak gene upregulation could be blocked by protein synthesis inhibitor cycloheximide. The GSIV-induced Bax/Bak-mediated cell death may reduce by the anti-apoptotic gene Bcl-xL in fish cells.